Preparation method of cobalt / nitrogen-doped graphite carbon / cadmium zinc sulfide heterojunction photocatalyst, product and application thereof

CN118616113BActive Publication Date: 2026-11-03ZHEJIANG NORMAL UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202410696103.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-31
Publication Date
2026-11-03
Estimated Expiration
2044-05-31

AI Technical Summary

Technical Problem

Existing photocatalysts exhibit weak CO2 adsorption and low separation efficiency of the photogenerating support during CO2 photoreduction, limiting their CO2 photoreduction performance. Furthermore, metal sulfides suffer from photocorrosion, hindering their widespread application.

Method used

By preparing cobalt/nitrogen-doped graphite carbon/cadmium sulfide zinc heterojunction photocatalysts, using ZIF-8@ZIF-67 as a template, and combining zinc acetate, cadmium acetate, and sodium sulfide to form a heterojunction structure, the light absorption capacity and the separation of photogenerated electron-hole pairs are optimized, thereby improving the photocatalytic CO2 reduction performance.

Benefits of technology

It achieves highly efficient photocatalytic reduction of CO2 to CH4, with good cycle stability and product selectivity, reduces preparation cost, and simplifies the synthesis route.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118616113B_ABST
    Figure CN118616113B_ABST
Patent Text Reader

Abstract

The application discloses a preparation method of a cobalt / nitrogen-doped graphite carbon / cadmium zinc sulfide heterojunction photocatalyst, and comprises the following steps: (1) calcining ZIF-8@ZIF-67 to obtain cobalt / nitrogen-doped graphite carbon; (2) dispersing the cobalt / nitrogen-doped graphite carbon as a template in a solvent, adding zinc acetate, cadmium acetate and sodium sulfide, and stirring in a water bath to obtain the cobalt / nitrogen-doped graphite carbon / cadmium zinc sulfide heterojunction photocatalyst. The application further discloses the cobalt / nitrogen-doped graphite carbon / cadmium zinc sulfide heterojunction photocatalyst prepared by the above preparation method and application of the photocatalyst in photocatalytic reduction of CO2 into methane. The preparation method is simple, and the photocatalyst prepared by the method has good performance and cycle stability when applied to photocatalytic reduction of CO2.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of photocatalytic CO2 reduction catalyst technology, and in particular to a method for preparing a cobalt / nitrogen-doped graphite carbon / cadmium sulfide zinc heterojunction photocatalyst, as well as its products and applications. Background Technology

[0002] Since the Industrial Revolution, the widespread use of fossil fuels has led to a rapid increase in the concentration of the greenhouse gas CO2 in the atmosphere, causing an imbalance in the Earth's graphitic carbon cycle and triggering a series of climate and environmental problems. Achieving carbon neutrality by controlling greenhouse gas emissions has become one of the major challenges facing society today, and utilizing renewable energy to drive catalytic reactions to produce clean energy is widely considered by academia and industry as an important strategy for solving these problems. Photocatalysis, as a sustainable, environmentally friendly, and promising method, has been widely accepted, addressing both energy shortages and environmental pollution. However, in the CO2 photoreduction process, the performance is still limited due to weak CO2 adsorption and low separation efficiency of the photogenerating carrier. Therefore, developing a photocatalyst to efficiently and artificially catalyze greenhouse gas CO2 and water into usable organic compounds such as CH4 and CO is one of the most ideal ways to simultaneously solve environmental pollution and the energy crisis.

[0003] Graphitized carbon materials are widely used in semiconductor composites to enhance photocatalytic activity due to their high electrical conductivity and excellent electron mobility to guide carrier movement. Furthermore, nitrogen doping can further enhance the electronic and chemical properties of graphitized carbon materials, thereby improving photocatalytic efficiency (https: / / doi.org / 10.1021 / acsami.8b04837, Phase Transformation Synthesis of Strontium Tantalum Oxynitride-Based Heterojunction for Improved Visible Light-Driven Hydrogen Evolution). On the other hand, cobalt, with its good electron-mediating ability, is the preferred component for preparing photoredox catalysts (https: / / doi.org / 10.1021 / jacs.8b10380, Selective CO2 Reduction Catalyzed by SingleCobalt Sites on Carbon Nitride under Visible-Light Irradiation). Besides adjusting the chemical composition, designing a suitable photocatalyst structure also strongly influences catalytic performance. Hollow photocatalysts possess a large specific surface area and abundant reaction sites, which can enhance the adsorption of reactants and promote surface-related redox reactions (https: / / doi.org / 10.1002 / adma.201801369). Furthermore, the thin-shell structure of the hollow support reduces the charge diffusion length, aiding in the separation and migration of electron-hole pairs. In addition, hollow particles, particularly polyhedral cages, can enhance solar energy utilization through intracavity reflection / scattering effects. Compared to conventional cadmium sulfide, zinc cadmium sulfide solid solutions exhibit lower photogenerated carrier recombination rates and controllable band structures (https: / / doi.org / 10.1002 / smll.202106420). However, all metal sulfides are subject to photocorrosion, severely limiting the widespread application of zinc cadmium sulfide photocatalysts.

[0004] Therefore, how to prepare a simple and easy synthetic route for the efficient photocatalytic reduction of CO2 to methane is currently a research hotspot in this field. Summary of the Invention

[0005] The purpose of this invention is to provide a method for preparing a cobalt / nitrogen-doped graphite carbon / cadmium sulfide zinc heterojunction photocatalyst, as well as its products and applications. The preparation method is simple, and the prepared photocatalyst exhibits good performance and cycle stability when applied to photocatalytic CO2 reduction.

[0006] This invention provides the following technical solution:

[0007] A method for preparing a cobalt / nitrogen-doped graphite carbon / cadmium sulfide zinc heterojunction photocatalyst, the method comprising the following steps:

[0008] (1) Cobalt / nitrogen-doped graphite carbon was obtained by calcining ZIF-8@ZIF-67;

[0009] (2) Cobalt / nitrogen-doped graphite carbon was dispersed in a solvent as a template, and zinc acetate, cadmium acetate, and sodium sulfide were added. The mixture was stirred in a water bath to obtain a cobalt / nitrogen-doped graphite carbon / cadmium sulfide zinc heterojunction photocatalyst (Co / NGC / CdZnS).

[0010] The preparation method provided by this invention is a simple and easy synthetic route. The prepared cobalt / nitrogen-doped graphite carbon / cadmium sulfide zinc heterojunction photocatalyst can optimize light absorption capacity and promote the separation efficiency of photogenerated electron-hole pairs, thereby improving the photocatalytic CO2 reduction performance and product selectivity (the hollow structure improves the utilization rate of visible light, and the construction of the heterojunction improves the photocatalytic efficiency and has good stability; the heterostructure can effectively inhibit photocorrosion and accelerate the separation of photogenerated carriers, thereby improving the activity and stability of the photocatalyst).

[0011] Preferably, in step (1), the preparation method of ZIF-8@ZIF-67 includes:

[0012] (1-1) Zinc acetate and 2-methylimidazole were dissolved in a solvent as reactants to synthesize ZIF-8.

[0013] (1-2) Using ZIF-8 as a template, cobalt nitrate and 2-methylimidazole were added respectively, and methanol was used as a solvent. The mixture was aged at room temperature to obtain ZIF-8@ZIF-67.

[0014] In step (1-1), the mass ratio of zinc acetate to 2-methylimidazole is 1:1–1:12. Preferably, in step (1-1), the mass ratio of zinc acetate to 2-methylimidazole is 1:3.

[0015] In step (1-1), the solvent can be methanol, ethanol, or deionized water.

[0016] In step (1-2), the mass ratio of ZIF-8, cobalt nitrate, and 2-methylimidazole is 1:2:2.26–1:2:9.32. Preferably, in step (1-2), the mass ratio of ZIF-8, cobalt nitrate, and 2-methylimidazole is 1:2:5.2.

[0017] This invention enables the generation of ZIF-8 and ZIF-8@ZIF-67 with a dodecahedral morphology by controlling the raw material mass ratio and solvent in the above steps.

[0018] The steps (1-2) are as follows: ZIF-8 and cobalt nitrate obtained in step (1-1) are dispersed in methanol and sonicated until homogeneous to obtain mixed solution A; then 2-methylimidazole is dispersed in methanol and sonicated until homogeneous to obtain solution B; then solution B is mixed with solution A and aged at room temperature for 4–24 h, washed with anhydrous ethanol, centrifuged, and dried in a forced-air drying oven at 60 °C.

[0019] The preparation method provided by the present invention further includes: dispersing the cobalt / nitrogen-doped graphite carbon after calcination in step (1) in hydrochloric acid solution and stirring at room temperature (to remove Co particles on the surface) to obtain pretreated cobalt / nitrogen-doped graphite carbon.

[0020] Preferably, in step (1), the calcination temperature is 110–150℃ and 800–1000℃, respectively, for 1–5 hours. This invention maintains the morphology of ZIF-8@ZIF-67 and prevents collapse by controlling the calcination temperature.

[0021] Further preferred calcination temperatures are 120℃ and 800–1000℃, respectively, for 2 hours, with a heating rate of 2℃ / min. Optimizing the calcination temperature, time, and heating rate improves the morphology retention of ZIF-8@ZIF-67.

[0022] In step (2), the solvent can be deionized water.

[0023] Preferably, in step (2), the molar ratio of zinc acetate, cadmium acetate and sodium sulfide is 1:(0.67–1.5):(2–3).

[0024] More preferably, the molar ratio of zinc acetate to cadmium acetate is 1:1.5.

[0025] Preferably, in step (2), the loading of cadmium sulfide zinc in the cobalt / nitrogen-doped graphite carbon / cadmium sulfide zinc heterojunction photocatalyst is 41–68%, and the percentage is a mass percentage.

[0026] More preferably, the loading of zinc cadmium sulfide in the cobalt / nitrogen-doped graphite carbon / zinc cadmium sulfide heterojunction photocatalyst is 41–52%. By optimizing the loading of zinc cadmium sulfide, the photocatalytic CO2 reduction performance and product selectivity can be further optimized.

[0027] The present invention also provides a cobalt / nitrogen-doped graphite carbon / cadmium sulfide zinc heterojunction photocatalyst obtained according to the above preparation method.

[0028] Preferably, the diameter of the cobalt / nitrogen-doped graphite carbon / cadmium sulfide zinc heterojunction hollow dodecahedral photocatalyst is 250-300 nm.

[0029] The present invention also provides an application of the above-mentioned cobalt / nitrogen-doped graphite carbon / cadmium sulfide zinc heterojunction photocatalyst in the photocatalytic reduction of CO2 to methane.

[0030] Compared with the prior art, the present invention has the following technical effects:

[0031] The preparation method of the cobalt / nitrogen-doped graphite carbon / cadmium sulfide zinc heterojunction photocatalyst provided by this invention has the advantages of high reproducibility, simple synthesis process, inexpensive raw materials, low photocatalyst preparation cost, easy control and high uniformity. The cobalt / nitrogen-doped graphite carbon / cadmium sulfide zinc heterojunction photocatalyst prepared by this invention has good catalytic performance, high cycle stability, and can be used for photocatalytic CO2 reduction, with high photocatalytic CO2 reduction performance and product selectivity, especially CH4 selectivity. Attached Figure Description

[0032] Figure 1 The XRD pattern of the product prepared in Example 1 is shown, where: the horizontal axis X is the diffraction angle (2θ), and the vertical axis Y is the relative diffraction intensity.

[0033] Figure 2 The image shows the morphology of the cobalt / nitrogen-doped graphite carbon / cadmium sulfide zinc heterojunction nanocomposite photocatalyst prepared in Example 1.

[0034] Figure 3 The image shows the Raman spectra of the cobalt / nitrogen-doped graphite carbon / cadmium sulfide zinc heterojunction nanocomposite material prepared in Example 1.

[0035] Figure 4 The results show the photocatalytic performance of the cobalt / nitrogen-doped graphite carbon / cadmium sulfide zinc heterojunction nanocomposite material prepared in Example 1, and the photocatalytic performance of the cobalt / nitrogen-doped graphite carbon and cadmium sulfide zinc nanoparticles in generating CH4 from CO2.

[0036] Figure 5 The results show the photocatalytic CO2 to CO production performance of the cobalt / nitrogen-doped graphite carbon / cadmium sulfide zinc heterostructure nanocomposite material prepared in Example 1.

[0037] Figure 6 The results show the photocatalytic CO2 reduction cycle performance test results of the cobalt / nitrogen-doped graphite carbon / cadmium sulfide zinc heterojunction photocatalyst prepared in Example 1. Detailed Implementation

[0038] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as a limitation of the present invention, but rather as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0039] It should be understood that the terminology used in this invention is merely for describing particular embodiments and is not intended to limit the invention. Furthermore, with respect to numerical ranges in this invention, it should be understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. Every smaller range between any stated value or intermediate value within a stated range, and any other stated value or intermediate value within said range, is also included in this invention. The upper and lower limits of these smaller ranges may be independently included or excluded from the range.

[0040] Unless otherwise stated, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art. While only preferred methods and materials have been described herein, any methods and materials similar or equivalent to those described herein may be used in the implementation or testing of this invention. All references to this specification are incorporated by way of citation to disclose and describe methods and / or materials associated with those references. In the event of any conflict with any incorporated reference, the content of this specification shall prevail.

[0041] Various modifications and variations can be made to the specific embodiments described in this specification without departing from the scope or spirit of the invention, as will be apparent to those skilled in the art. Other embodiments derived from this specification will also be readily apparent to those skilled in the art. This specification and embodiments are merely exemplary.

[0042] The terms “include,” “including,” “have,” “contain,” etc., used in this article are all open-ended terms, meaning that they include but are not limited to.

[0043] The X-ray diffractometer used in this embodiment of the invention is a Bruker D8 X-ray diffractometer (USA), and the scanning electron microscope used is a Zeiss GeminiSEM 300 field emission scanning electron microscope (FE-SEM) (Germany). Raman spectra were acquired on a LabRAM HR Evolution Raman spectrometer with an excitation light of 532 nm.

[0044] The photocatalytic CO2 reduction performance was characterized using the following method in the embodiments of the present invention:

[0045] Photocatalytic CO2 reduction test: 5 mg of photocatalyst was dispersed in 2 ml of water and sonicated for 5 min until homogeneous to obtain a mixture. The mixture was then dispersed on a 40 mm glass fiber filter membrane and dried in a 60 °C oven. The glass fiber filter membrane containing the sample was fixed on a tripod and placed in a Pyrex reaction vessel along with 2 ml of deionized water. The reaction vessel was evacuated three times, and then high-purity CO2 (99.999%) was pumped in to approximately 80 kPa. The temperature of the entire reaction system was maintained at 25 °C by circulating condensate. Gas phase products were collected every 0.5 h and analyzed using an online gas chromatograph equipped with a flame ionization detector (FID) and a thermal conductivity detector (Shimadzu GC-2014 gas chromatograph, Ar as carrier gas) to detect the relevant gas types and contents. The photocatalytic CO2 reduction cycle stability test was basically the same as the above operation, except that after every 4 h of testing, the vacuum was re-evacuated and then high-purity CO2 gas was pumped in to avoid affecting the accuracy of the next detection.

[0046] Example 1

[0047] The preparation method of the cobalt / nitrogen-doped graphite carbon / cadmium sulfide zinc heterojunction hollow dodecahedral photocatalyst provided in this embodiment mainly includes the following steps:

[0048] (1) Preparation of ZIF-8

[0049] 1.76 g of zinc acetate (Zn(CH3COO)2·2H2O) and 5.24 g of 2-methylimidazole were added to 200 ml of anhydrous methanol and mixed. The mixture was then sonicated until homogeneous. The two were then mixed to obtain a mixed solution, which was magnetically stirred for 24 h. The solution was washed with anhydrous ethanol, centrifuged, and dried in a 60 °C forced-air drying oven to synthesize ZIF-8.

[0050] (2) Preparation of ZIF-8@ZIF-67

[0051] 50 mg ZIF-8 was dispersed in 5 ml of anhydrous methanol, and 93.8 mg of cobalt nitrate (Co(NO3)2·6H2O) was added. The mixture was sonicated for 5 min until homogeneous to obtain solution A. Then, 262.8 mg of 2-methylimidazole was dispersed in 5 ml of anhydrous methanol and sonicated until homogeneous to obtain solution B. Solution B was then poured into solution A, mixed thoroughly, aged at room temperature for 4 h, washed with anhydrous ethanol, centrifuged, and dried in a 60 °C forced-air drying oven to obtain ZIF-8@ZIF-67.

[0052] (3) Preparation of cobalt / nitrogen-doped graphite carbon

[0053] The ZIF-8@ZIF-67 obtained in step (2) was calcined at 120℃ and 800℃ for 2 hours in a nitrogen atmosphere (heating rate of 2℃ / min) to obtain cobalt / nitrogen-doped graphite carbon hollow dodecahedrons; then 50 mg of cobalt / nitrogen-doped graphite carbon hollow dodecahedrons were dispersed in 3M hydrochloric acid solution, sonicated until uniformly mixed, stirred at room temperature for 12 hours, washed with anhydrous ethanol and centrifuged, and dried in a 60℃ forced-air drying oven to obtain cobalt / nitrogen-doped graphite carbon.

[0054] (4) Preparation of cobalt / nitrogen-doped graphite carbon / cadmium sulfide zinc heterojunction-10

[0055] 10 mg of cobalt / nitrogen-doped graphite carbon treated with hydrochloric acid was dispersed in 60 ml of deionized water and sonicated for 15–20 min until homogeneous. 0.1 mmol zinc acetate (Zn(CH3COO)2·2H2O), 0.15 mmol cadmium acetate (Cd(CH3COO)2·2H2O), and 0.3 mmol sodium sulfide (Na2S·9H2O) were added to the above mixed solution and stirred in an 80 °C water bath for 2 h. Then, impurities were removed by centrifugation with deionized water and anhydrous ethanol multiple times. Finally, the collected precipitate was dried at 60 °C for 12 h to obtain a cobalt / nitrogen-doped graphite carbon / cadmium sulfide zinc heterojunction Co / NGC / CdZnS, which is denoted as cobalt / nitrogen-doped graphite carbon / cadmium sulfide zinc heterojunction-10 in this example.

[0056] The ZIF-8 obtained in this embodiment has a regular dodecahedral morphology, the ZIF-8@ZIF-67 has a dodecahedral morphology, and the cobalt / nitrogen-doped graphite carbon and cobalt / nitrogen-doped graphite carbon / zinc cadmium sulfide heterojunction are hollow dodecahedrals.

[0057] In this embodiment, the loading of cadmium sulfide zinc in the cobalt / nitrogen-doped graphite carbon / cadmium sulfide zinc heterojunction-10 photocatalyst is 68%.

[0058] The XRD test results of the cobalt / nitrogen-doped graphite carbon / cadmium sulfide zinc heterojunction-10 photocatalyst prepared in this embodiment show that: Figure 1 As shown, the horizontal axis X is the diffraction angle (2θ), the vertical axis Y is the relative diffraction intensity, and its diffraction peaks correspond to single cobalt / nitrogen-doped graphite carbon, zinc cadmium sulfide, and cobalt / nitrogen-doped graphite carbon / zinc cadmium sulfide heterojunctions.

[0059] Field emission scanning electron microscopy (FESEM) analysis was performed on the cobalt / nitrogen-doped graphite carbon / cadmium sulfide zinc heterojunction-10 photocatalyst prepared in this embodiment. The resulting electron micrographs are shown below. Figure 2 As shown, a heterostructure with nanoparticles loaded on the surface of a hollow dodecahedron can be seen. The cobalt / nitrogen-doped graphite carbon / cadmium sulfide zinc heterojunction-10 photocatalyst prepared in this embodiment has a diameter range of 250-300 nm.

[0060] The photocatalytic CO2 reduction to CO and CH4 performance of the cobalt / nitrogen-doped graphite carbon / cadmium sulfide zinc heterojunction-10 photocatalyst prepared in this embodiment was tested as follows: Figure 4 and Figure 5 As shown, under visible light irradiation, its photocatalytic reduction rates of CO2 to CO and CH4 are 10.03 μmol g, respectively. -1 h -1 and 7.24 μmol g -1 h -1 The selectivity for photocatalytic CO2 reduction to CH4 was 41.93%.

[0061] Example 2: Preparation of Cobalt / Nitrogen-Doped Graphite Carbon / Cadmium Sulfide Zinc Heterojunction-20

[0062] As described in Example 1, the difference between this example and Example 1 is that:

[0063] Cobalt / nitrogen-doped graphite carbon treated with 20 mg of hydrochloric acid was dispersed in 60 ml of deionized water and sonicated for 15–20 min until homogeneous. 0.1 mmol zinc acetate (Zn(CH3COO)2·2H2O), 0.15 mmol cadmium acetate (Cd(CH3COO)2·2H2O), and 0.3 mmol sodium sulfide (Na2S·9H2O) were added to the above mixed solution and stirred in an 80 °C water bath for 2 h. Then, impurities were removed by centrifugation with deionized water and anhydrous ethanol multiple times. Finally, the collected precipitate was dried at 60 °C for 12 h to obtain a cobalt / nitrogen-doped graphite carbon / cadmium sulfide zinc heterojunction Co / NGC / CdZnS, which is denoted as cobalt / nitrogen-doped graphite carbon / cadmium sulfide zinc heterojunction-20 in this example.

[0064] The morphology of the cobalt / nitrogen-doped graphite carbon / cadmium sulfide zinc heterojunction-20 prepared in this embodiment is also a hollow dodecahedron.

[0065] In this embodiment, the loading of cadmium sulfide zinc in the cobalt / nitrogen-doped graphite carbon / cadmium sulfide zinc heterojunction-20 photocatalyst is 52%.

[0066] Raman spectroscopy analysis was performed on the cobalt / nitrogen-doped graphite carbon / cadmium sulfide zinc heterojunction-20 photocatalyst prepared in this embodiment, as follows: Figure 3 As shown, the D and G bands of cobalt / nitrogen-doped graphite carbon can be observed. The G band is a typical Raman peak for graphite materials.

[0067] The photocatalytic CO2 reduction to CO and CH4 performance of the cobalt / nitrogen-doped graphite carbon / cadmium sulfide zinc heterojunction-20 photocatalyst prepared in this embodiment is as follows: Figure 4 and Figure 5 As shown: Under visible light irradiation, the photocatalytic reduction rates of CO2 to CO and CH4 were 9.06 μmol g, respectively.-1 h -1 and 35.67 μmol g -1 h -1 The selectivity for photocatalytic CO2 reduction to CH4 was 79.75%.

[0068] The photocatalytic CO2 reduction cycle performance of the cobalt / nitrogen-doped graphite carbon / cadmium sulfide zinc heterojunction-20 photocatalyst prepared in this embodiment was tested as follows: Figure 6 As shown, its photocatalytic CO2 reduction test can be stably and continuously maintained for 20 hours under visible light.

[0069] Example 3: Preparation of Cobalt / Nitrogen-Doped Graphite Carbon / Cadmium Sulfide Zinc Heterojunction-30

[0070] As described in Example 1, the difference between this example and Example 1 is that:

[0071] Cobalt / nitrogen-doped graphite carbon treated with 30 mg of hydrochloric acid was dispersed in 60 ml of deionized water and sonicated for 15–20 min until homogeneous. 0.1 mmol zinc acetate (Zn(CH3COO)2·2H2O), 0.15 mmol cadmium acetate (Cd(CH3COO)2·2H2O), and 0.3 mmol sodium sulfide (Na2S·9H2O) were added to the above mixed solution and stirred in an 80 °C water bath for 2 h. Then, impurities were removed by centrifugation with deionized water and anhydrous ethanol multiple times. Finally, the collected precipitate was dried at 60 °C for 12 h to obtain a cobalt / nitrogen-doped graphite carbon / cadmium sulfide zinc heterojunction Co / NGC / CdZnS, which is denoted as cobalt / nitrogen-doped graphite carbon / cadmium sulfide zinc heterojunction-30 in this example.

[0072] The morphology of the cobalt / nitrogen-doped graphite carbon / cadmium sulfide zinc heterojunction-30 prepared in this embodiment is also a hollow dodecahedron.

[0073] In this embodiment, the loading of cadmium sulfide zinc in the cobalt / nitrogen-doped graphite carbon / cadmium sulfide zinc heterojunction-30 photocatalyst is 41%.

[0074] The photocatalytic CO2 reduction to CO and CH4 performance of the cobalt / nitrogen-doped graphite carbon / cadmium sulfide zinc heterojunction-30 photocatalyst prepared in this embodiment is as follows: Figure 4 and Figure 5 As shown: Under visible light irradiation, the photocatalytic reduction rates of CO2 to CO and CH4 are 8.35 μmol g, respectively. -1 h -1 and 24.44 μmol g -1 h -1 The selectivity for photocatalytic CO2 reduction to CH4 was 74.45%.

[0075] Example 4: Preparation of Cobalt / Nitrogen-Doped Graphite Carbon / Cadmium Sulfide Zinc Heterojunction - 1:1.5

[0076] As described in Example 1, the difference between this example and Example 1 is that:

[0077] Cobalt / nitrogen-doped graphite carbon treated with 20 mg of hydrochloric acid was dispersed in 60 ml of deionized water and sonicated for 15–20 min until homogeneous. 0.15 mmol zinc acetate (Zn(CH3COO)2·2H2O), 0.1 mmol cadmium acetate (Cd(CH3COO)2·2H2O), and 0.3 mmol sodium sulfide (Na2S·9H2O) were added to the mixture. The mixture was stirred in an 80°C water bath for 2 h. Impurities were removed by repeated centrifugation with deionized water and anhydrous ethanol. Finally, the collected precipitate was dried at 60°C for 12 h to obtain a cobalt / nitrogen-doped graphite carbon / cadmium sulfide zinc heterojunction Co / NGC / CdZnS, denoted in this example as cobalt / nitrogen-doped graphite carbon / cadmium sulfide zinc heterojunction-1:1.5.

[0078] The cobalt / nitrogen-doped graphite carbon / cadmium sulfide zinc heterojunction-1:1.5 prepared in this embodiment also has a hollow dodecahedron morphology.

[0079] The cobalt / nitrogen-doped graphite carbon / cadmium sulfide zinc-1:1.5 photocatalyst prepared in this embodiment exhibits the following photocatalytic performance in reducing CO2 to CO and CH4: under visible light irradiation, the photocatalytic reduction rates of CO2 to CO and CH4 are 6.23 μmol g, respectively. -1 h -1 and 3.84 μmol g -1 h -1 The selectivity for photocatalytic CO2 reduction to CH4 was 38.13%.

[0080] Example 5: Preparation of Cobalt / Nitrogen-Doped Graphite (Graphite Carbon / Cadmium Sulfide Zinc-1:1)

[0081] As described in Example 1, the difference between this example and Example 1 is that:

[0082] Cobalt / nitrogen-doped graphite carbon treated with 20 mg of hydrochloric acid was dispersed in 60 ml of deionized water and sonicated for 15–20 min until homogeneous. 0.1 mmol zinc acetate (Zn(CH3COO)2·2H2O), 0.1 mmol cadmium acetate (Cd(CH3COO)2·2H2O), and 0.3 mmol sodium sulfide (Na2S·9H2O) were added to the above mixed solution and stirred in an 80 °C water bath for 2 h. Then, impurities were removed by centrifugation with deionized water and anhydrous ethanol multiple times. Finally, the collected precipitate was dried at 60 °C for 12 h to obtain a cobalt / nitrogen-doped graphite carbon / cadmium sulfide zinc heterojunction Co / NGC / CdZnS, which in this example is denoted as cobalt / nitrogen-doped graphite carbon / cadmium sulfide zinc heterojunction-1:1.

[0083] The cobalt / nitrogen-doped graphite carbon / cadmium sulfide zinc heterojunction-1:1 prepared in this embodiment also has a hollow dodecahedron morphology.

[0084] The cobalt / nitrogen-doped graphite / zinc cadmium sulfide-1:1 photocatalytic CO2 reduction to CO and CH4 prepared in this embodiment exhibits the following performance: Figure 4 and Figure 5 As shown: Under visible light irradiation, the photocatalytic reduction rates of CO2 to CO and CH4 are 6.01 μmol g, respectively. -1 h -1 and 3.19 μmol g -1 h -1 The selectivity for photocatalytic CO2 reduction to CH4 was 34.67%.

[0085] Comparative Example 1: Preparation of Cadmium Zinc Sulfide Nanoparticles

[0086] As described in Example 1, the difference between this comparative example and Example 1 is that:

[0087] During ultrasonic dispersion, 0.5 mmol of zinc acetate and 0.75 mmol of cadmium acetate were added to 60 ml of deionized water. After ultrasonic dispersion, the mixture was magnetically stirred for 10–15 min. Immediately afterwards, 1.5 mmol of sodium sulfide was added, and the mixture was ultrasonically dispersed until homogeneous. The mixture was then stirred in an 80°C water bath for 2 h. Impurities were removed by centrifugation with deionized water and anhydrous ethanol multiple times. Finally, the collected precipitate was dried at 60°C for 12 h.

[0088] The photocatalytic CO2 reduction to CO and CH4 performance of the zinc cadmium sulfide nanoparticles prepared in this comparative example is as follows: under visible light irradiation, the photocatalytic CO2 reduction to CO and CH4 rates are 5.03 μmol g, respectively. -1 h -1 and 0.77 μmol g -1 h -1The selectivity for photocatalytic CO2 reduction to CH4 was 13.29%.

[0089] The embodiments described above are merely preferred embodiments of the present invention and are not intended to limit the scope of the present invention. Various modifications and improvements made by those skilled in the art to the technical solutions of the present invention without departing from the spirit of the present invention should fall within the protection scope defined by the claims of the present invention.

Claims

1. The application of a cobalt / nitrogen-doped graphite carbon / cadmium sulfide zinc heterojunction photocatalyst in the photocatalytic reduction of CO2 to methane, characterized in that, The preparation method of cobalt / nitrogen-doped graphite carbon / cadmium sulfide zinc heterojunction photocatalyst includes the following steps: (1) Cobalt / nitrogen-doped graphite carbon was obtained by calcining ZIF-8@ZIF-67; In step (1), the preparation method of ZIF-8@ZIF-67 includes: (1-1) Zinc acetate and 2-methylimidazole were dissolved in a solvent as reactants to synthesize ZIF-8; (1-2) Using ZIF-8 as a template, cobalt nitrate and 2-methylimidazole were added respectively, dissolved in a solvent, and aged at room temperature to obtain ZIF-8@ZIF-67; (2) Cobalt / nitrogen-doped graphite carbon was dispersed in a solvent as a template, and zinc acetate, cadmium acetate and sodium sulfide were added. The mixture was stirred in a water bath to obtain a cobalt / nitrogen-doped graphite carbon / cadmium sulfide zinc heterojunction photocatalyst. The loading of cadmium sulfide zinc in the cobalt / nitrogen-doped graphite carbon / cadmium sulfide zinc heterojunction photocatalyst is 41-68%, and the percentage is a mass percentage. The cobalt / nitrogen-doped graphite carbon / cadmium sulfide zinc heterojunction photocatalyst is a hollow dodecahedron with a diameter of 250~300nm.

2. The application according to claim 1, characterized in that, In step (1-1), the mass ratio of zinc acetate to 2-methylimidazole is 1:1–12.

3. The application according to claim 1, characterized in that, In steps (1-2), the mass ratio of ZIF-8, cobalt nitrate, and 2-methylimidazole is 1:2:2.26–1:2:9.

32.

4. The application according to claim 1, characterized in that, The preparation method includes: dispersing the cobalt / nitrogen-doped graphite carbon after calcination in step (1) in a hydrochloric acid solution and stirring at room temperature to obtain pretreated cobalt / nitrogen-doped graphite carbon.

5. The application according to claim 1, characterized in that, In step (1), the calcination is a two-step calcination, with calcination temperatures of 110–150 ℃ and 800–1000 ℃, and calcination for 1–5 h respectively.

6. The application according to claim 1, characterized in that, In step (2), the molar ratio of zinc acetate, cadmium acetate and sodium sulfide is 1:(0.67–1.5):(2–3).

Citation Information

Patent Citations

  • Preparation method of tubular C3N4 / Cd0.5Zn0.5S composite photocatalyst

    CN108855186A